On the role of magnetising frequency and magnetic field intensity on hysteresis loop characteristics. (2017) - Srivastava, Ashish; Kumar, Harikishor; Yusufzai, Mohd. Zaheer Khan; Vashista, Meghanshu
The goal of present research work is to study the variation in the shape of hysteresis loop owing to change in the analysis parameter i.e., magnetising frequency and applied magnetic field strength upon pack carburised low carbon steel samples. Pack carburised heat treatment performed at three different temperatures to induce varying hardness into steel samples. Hysteresis loop characteristics such as coercivity, permeability, power loss and remanence were measured in a wide range of magnetising frequency and magnetic field intensity. Coercivity is observed to increase with increase in magnetising frequency and applied field strength. In low-frequency range (<1 Hz), remanence and power loss were found to decrease, with an increase in frequency, in a contrary, increase in frequency in high-frequency range (>1 Hz) results into increase in remanence and power loss. However, with an increase in magnetic field strength both remanence and power loss were found to increase.